Motivation and morality : a multidisciplinary approach - Berg, Martha K.; Chang, Edward C. (Edward Chin-Ho) (American Psychological Association, 2023)
"What drives us to do good things, and to avoid doing bad? This book offers an integrative examination of the role of motivation in shaping moral cognition, judgement, and behavior"--